Effects of physical training on glycosylated hemoglobin levels in patients with Type II Diabetes Mellits - Masotti, M. Alexander (My University, 1986)
The purpose of this study was to determine the effectiveness of bicycle ergometry (30 min per day, 7 days a week, for 12 weeks) on levels of glycosylated hemoglobin, an index of glycemic control, in Type II diabetics. The 28 volunteers were separated into three groups: (1) exercise (n=9), (2) exercise with dietary supplement (n=9), and (3) control (n=10). The purpose of Group 2 was to control for weight loss, thus isolating the physical training effects. The null hypothesis was that there would be no significant differences in glycosylated hemoglobin levels over the treatment period within and between the groups. The mean glycosylated hemoglobin levels in all groups significantly decreased at the p < .05 level; Group 1 (9.17 x 2.26 to 7.76 .x 2.35 %), Group 2 (9.47 + 3.03 to 8.62 x 2.76%), and Group 3 (10.90 + 4.88 to 10.27 + 4.71 %), despite there being no significance between groups. Even though differences between groups were not significant, Group 1 approached the normal range (4.6-7.6 %) set by the Gundersen Clinic blood laboratory. Metabolic complications did not arise in any participant during the study and increased physical training did not produce pronounced weight loss. Therefore, exercise as a supplement to a proper diet could be the most beneficial treatment for Type II diabetics.
Keywords: Diabetes; Exercise -- Physiological aspects